Nephron prorenin receptor deficiency alters renal medullary endothelin-1 and endothelin receptor expression - Ramkumar, N; Stuart, D; Abraham, N; Kohan, D E (Physiological research, 2018)
The endothelin (ET) and prorenin/renin/prorenin receptor (PRR) systems have opposing physiological effects on collecting duct (CD) salt and water reabsorption. It is unknown if the CD ET and renin/PRR systems interact, hence we examined the effects of deleting CD renin or nephron PRR on CD ET system components. PRR knockout (KO) mice were polyuric and had markedly increased urinary ET-1 and inner medullary CD (IMCD) ET-1 mRNA. PRR KO mice had greatly increased IMCD ETA receptor mRNA and protein, while ETB mRNA and protein were decreased. Water loaded wild-type mice with similar polyuria as PRR KO mice had modestly increased urinary ET-1 excretion and inner medullary ET-1 mRNA, while inner medullary ETA and ETB mRNA or protein expression were unaffected. In contrast to PRR KO, CD prorenin/renin KO did not alter ET system components. Taken together, these results suggest that the nephron PRR is involved in regulating CD ET system expression, but this effect may be independent of CD-derived renin.
Keywords: nefrony; Prorenin Receptor; Receptors, Cell Surface; myši inbrední C57BL; receptor endotelinu B; Kidney Medulla; Mice; Endothelin-1; endotelin-1; myši knockoutované; dřeň ledvin; zvířata; Nephrons; Receptor, Endothelin B; Mice, Knockout; myši; receptory buněčného povrchu; receptor endotelinu A; Receptor, Endothelin A; Mice, Inbred C57BL; receptor proreninu; Animals